Molecular changes in the phosphatidylinositide 3‐kinase (PI3K) pathway are common in gastric cancer. Issue 2 (28th June 2013) - Tran, Thang N.; Brettingham‐Moore, Kate; Duong, Cuong P.; Mitchell, Catherine; Clemons, Nicholas J.; Phillips, Wayne A.
Abstract Background and Objectives The phosphatidylinositide 3‐kinase (PI3K) pathway is an important signalling pathway that is frequently activated in cancer cells. This has led to the emergence of PI3K inhibitors as potential new treatment modalities for many cancers. We have investigated the frequency of molecular changes in the PI3K pathway in gastric cancer. Methods A series of sixty one human gastric cancer specimens and nine human gastric cancer cell lines were screened for PIK3CA mutations and copy number gain by direct sequencing and multiplex ligation‐dependent probe amplification (MLPA), respectively. PTEN protein levels were assessed by immunohistochemistry. Results Alterations in the PI3K pathway were found in 33 of 61 (54%) gastric tumours. PIK3CA mutation and copy number gain were detected in 3 (4.9%) and 8 (13.1%), respectively, of 61 gastric cancer samples while PTEN loss was detected in 24 (39%) of the tumours. Two tumours had both PTEN loss and PIK3CA copy number gain. There were no significant associations between these PI3K pathway changes and the clinical features of the tumours. Conclusions Alterations in the PI3K pathway are frequent in gastric tumours implicating this pathway as a legitimate therapeutic target in gastric cancer. J. Surg. Oncol. 2013; 108:113–120. © 2013 Wiley Periodicals, Inc.